Using Community-Based Participatory Research to Explore Food Insecurity in African American Adults. Issue 3 (3rd May 2020) - Paschal, Angelia M.; Mitchell, Jermaine B.; Burton, Wanda M.; Nickelson, Jen; Murphy, Pillar Z.; Ford, Frances
ABSTRACT: Background : Food insecurity is an ongoing national problem and is linked to chronic diseases and other poor health outcomes. Concerning are the rates in racial and ethnic minorities. Food insecurity is significantly high in African Americans older adults. Purpose : The purpose of this study was to use a Community-Based Participatory Research approach to assess the extent of food insecurity and associated factors in a sample of African American adults. Methods : A cross-sectional study design with purposive, convenience sampling was used. The survey included the 10-item USDA Food Security Module, fruit and vegetable intake questions, and sociodemographic items. Results : Results indicated that food insecurity was very high and was associated with being ≥65 years old, not having a spouse/partner, living alone, and residing in an urban location. Discussion : The CBPR approach resulted in changes to the survey, engaged community partners, access to a vulnerable population, and plans to build on the findings to address food insecurity in the community. Further research is needed to examine the associated factors. Translation to Health Education Practice : Given the complex nature of food insecurity and the findings from this study, research that engage the community and focus on multilevel interventions are recommended.